DAMPAK ADOPSI STANDAR PELAPORAN KEUANGAN INTERNASIONAL DAN SISTEM BUSINES NASIONAL TERHADAP MANAGEMEN LABA SERTA KONSEKUENSINYA TERHADAP DAYA DETEKSI AUDITOR - , Sri Suryaningsum, SE.,Ak.,M.Si.; , Prof. Dr. Jogiyanto Hartono M., Ak., M.B.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
ThisresearchevokestheissueofTheImpactoftheMandatoryAdoptionoftheInternationalFinancialReportingStandards(SPKI/IFRS)andtheStateâsBusinessSystemagainstboththeEarningsManagementandtheAuditorâsDetectingPowerConsequence.WecategorizetheIFRSintotwolevels,thatis,post-IFRSandpre-IFRS.Thepost-IFRSbasedontheprinciple,whilethepre-IFRSbasedontherule.Theprinciplebasisenablesmanagerstorunabroadenedprofessionalpolicyfreelycomparingwiththerulebasis,withtheresultthatthepost-IFRSconditionenablesthemanagerstogetabiggerEarningsManagementopportunity. TheBusinessSystemwascategorizedintoAngloBusinessSystemandContinentalBusinessSystem.TheAngloBusinessSystemhasatransparentandlessconservativecharacter,whiletheContinentalBusinessSystemhasaconfidentialandveryconservativecharacter.TheconfidentialcharacteroftheContinentalenablesthemanagerstogetbiggerEarningsManagement. ThebiggerEarningsManagementneedshigherAuditorâsDetectingPowerduetothemorecomplicatedofauditorâstask.TheAuditorâsDetectingPowerattachedonauditorâsquality. TheresearchtooksamplesofcompaniesinAsiaintheyear2000to2009.IttooktenyearstoprovewhethertheEarningsManagementâschangesexistornot.Thetestingonresearchhypothesisusedthescaleoftime2000to2009.ThetimewaschosenuponconsideringthebiasoftheIFRSperformancetransitiontoadopt.Thecollateraltestingappliedonsuspectingcompaniesgroupfrom2007to2009andontheentirecompaniesfortenyearstimeofscale(2000to2009). ThemandatoryoftheIFRSwastestedbasedontwogroups,thatis,thecountriesofthepost-IFRSandthecountriesofthepre-IFRS.ResearchingtheBusinessSystembasedontwogroups,thatis,theAngloSystem-CountriesandtheContinentalSystem-Countries.MeasuringtheEarningsManagementbasedontheAccrualActivitiesandtheRealActivities. ThetestingresultconcludedthattheEarningsManagementshiftdidnâtexistonboththeAccrualActivitiesandtheRealActivitiesforthefirstgrou(post-IFRS&Anglo)andthefourthgroup(pre-IFRS&Continental).TheAccrualEarningsManagementgoesdownmoreandmoremerelyoccurredonthethirdgroup(pre-IFRS&Anglo). HypothesisoneestimatedbiggerintervaloftheEarningsManagementonthepost-IFRSâcountriesgroupratherthanonthepre-IFRSâcountriesgroup.HypothesistwoestimatedbiggerintervaloftheEarningsManagementonContinentalSystemBusinessCountriesratherthantheAngloBusinessSystemountries.TheseEarningsManagementinhypothesisoneandhypothesistwowereexaminedthroughtwomeasurementsbasis,thatis,theAccrualActivityandtheRealActivity.Hypothesisoneandhypothesistwoweretestedthrought-testsampleindependentanalysistool. HypothesisthreeestimatedanintervaloftheEarningsManagementamongstcells.ThecellswereemergedbasedontheMandatoryAdoptionoftheIFRSandontheBusinessSystembecomingfourcells,thatis,thepost-IFRS&Anglo